AWARENESSABOUT CLEAN INDIA PROGRAMME AMONG PROSPECTIVE TEACHERS IN TIRUNELVELI DISTRICT - Raja, M.; Anitha, S. (International Journal of Research -GRANTHAALAYAH, 2017)
In this study the investigator made an attempt to find out the awareness about Clean India Programme of prospective teachers in Tirunelveli District with respect to their gender, locality, type of family, type of college, religion, age, parental income. Survey method was adopted for the study. Using simple random sampling technique the investigators selected a sample of 60 prospective teachers as sample foe analysis. The findings revealed that the prospective teachers did not differ in their awareness about clean India programme with respect to the gender, location of the college, type of the family, type of the college, religion, age and parental income. Thus we conclude that the prospective teachers in Tirunelveli district have no significant difference in their awareness about Clean India programme. The level of awareness about Clean India Programme was at moderate level.